A non-randomized pilot study to test the feasibility of treating chronic pain and opioid prescription use in rural areas with acceptance and commitment therapy (T-PACT). Issue 5 (24th October 2020) - Rhyne, Robert L; Rishel Brakey, Heidi; Halladay, Jacquie R.; Mottus, Kathleen; Greiner, K. Allen; Salt, Elizabeth; Myers, Orrin; Sutton, Kent; Fuentes, Jesus; Vowles, Kevin E.
Abstract: Chronic non-cancer pain (CNCP) involves one-third of the US population, and prescription opioids contribute to the opioid epidemic. The Centers for Disease Control and Prevention emphasizes maximizing non-opioid treatment, but many rural populations cannot access alternative therapies. Clinical and Translational Science Award hubs across four rural states performed a multi-site, single-arm intervention feasibility study testing methods and procedures of implementing a behavioral intervention, acceptance and commitment therapy, in primary care CNCP patients on chronic opioids. Using the CONSORT extension for feasibility studies, we describe lessons learned in recruiting/retaining participants, intervention implementation, data measurement, and multi-site procedures. Results inform a future definitive trial and potentially others conducting rural trials.